Spatiotemporal patterns of catch and discards of the Israeli Mediterranean trawl fishery in the early 1990s: ecological and conservation perspectives - Edelist, Dor; Sonin, Oren; Golani, Daniel; Rilov, Gil; Spanier, Ehud (Scientia Marina, 2011)
The spatiotemporal patterns of discards and catch composition of Israeli trawlers were examined using a 4-year (1990-1994), 324 haul dataset. Haul depth was found to be the main grouping variable for hauls, although significant seasonal differences were also found. 28.3% of the total catch was discarded, and there was a 40.1% discard percentage in shallow hauls. According to these figures, annual discards for the Israeli trawl fleet for the study period are estimated at ca. 440 to 700 t. Both the biomass and the number of discarded specimens peaked in summer, as well as the percentage of juvenile fish of commercial species. These findings suggest that a summer moratorium on trawling would reduce discards. The percentage of specimens of Indo-Pacific origin decreased from 51% in depths shallower than 37 m to 24% between 38 and 73 m, and 8% in deeper strata. Discards along the Israeli coast were comparable to those observed elsewhere in the Mediterranean. The findings presented here are the first quantitative account of fish community assemblages in the nearshore waters of the easternmost part of the Mediterranean, and thus provide valuable information for comparisons with more current datasets that are currently being assembled.